The promotion of a racially integrated Catholic community at King William's Town : challenges and opportunities - Fahy, Paul (Rhodes University, Faculty of Divinity, Department of Divinity, 1988)
Taking as its point of departure the model of the Church as a sacrament of unity, this study explores its implications for the fostering of a racially integrated Catholic community within an apartheid society. The particular context within which the investigation is conducted is the Sacred Heart Church, King William's Town, where the writer is pastor to a multiracial congregation. A dialogical approach is adopted between theology and praxis, in terms of which the data from a social analysis of the community are brought into a creative dialogue with the Vatican II vision of the Church. Findings from the analysis show that the attitudes of congregants to a racially integrated community are generally ambivalent. Historical, theological, psychosocial and political factors are seen to play an important role in shaping these attitudes. Arising from the dialogue between theology and praxis, the model of a pilgrim Church suggests itself as more relevant and realistic. This model constitutes a proximate goal. The sacrament model of the Church provides direction and focus for the pilgrim Church and is viewed as the ultimate goal. These models must be seen as complementary. The study concludes with a pastoral plan aimed at attaining the goals described. The main thrust of this plan is directed at changing congregants' attitudes to a racially integrated community. The strategies suggested involve the motivation of congregants to become actively involved, the transformation of congregants' attitudes, the promotion of a positive attitude to conflict and the challenging of apartheid structures. A differential approach is suggested in the pursuit of these objectives. A final conclusion to be drawn from this study is that the search for community is never-ending and that the fostering of a racially integrated Catholic community is a slow and painful process.
Keywords: Apartheid -- South Africa -- Religious aspects -- Catholic Church